Archaeal Diversity from Hydrothermal Systems of Deception Island, Antarctica - Blamey-Alegria, J; Pugin, B (2013)
Antarctica is an extreme continent composed of cold environments but also of several geothermal sites, among them is Deception Island, an active stratovolcano located in the South Shetland archipelago. From this island, few microbiological studies have been performed, and the presence of archaea has not been reported. In order to investigate the archaeal diversity in hydrothermalism from Deception Island, different submarine samples were taken from the flooded caldera. Samples were analyzed by denaturing gradient gel electrophoresis (DGGE) of the 16S rRNA gene in conjunction with culture-dependent methods at hyperthermophilic temperatures. Analysis from DGGE band sequencing showed the presence of archaea belonging to the hyperthermophilic genus Thermococcus and different uncultured archaea closely related to environmental clones from hydrothermal vents. Archaea from the psychrotolerant genus Methanococcoides were also detected. Additionally, we have successfully isolated an anaerobic hyperthermophilic archaeon closely related to Thermococcuscelericrescens. Cells were irregular cocci with a diameter between 0. 6 and 2 ?m and grew at 50-90 °C and at a NaCl concentration of 1-5 %. Here, we present, based on culture-dependent and culture-independent approaches, the first report on archaea from marine hydrothermal sites of Antarctica. © 2012 Springer-Verlag Berlin Heidelberg.